Why do some students want to be actively involved as peer educators, while others do not? Findings from NoTrap! anti-bullying and anti-cyberbullying program. Issue 4 (4th July 2019) - Zambuto, Valentina; Palladino, Benedetta Emanuela; Nocentini, Annalaura; Menesini, Ersilia
Abstract: The present study aims to explore if students who voluntarily decide to become peer educators in an anti-bullying program differ from their classmates who don't take on this role. 524 Italian students (age 13–18; males = 57%), completed self-report questionnaires at the pre-test measure of the NoTrap! anti-bullying program. In a following step, 118 of them voluntarily decided to become peer educators. Probit regression separate for gender, showed that male peer educators have a higher level of victimization, perceived support from friends and prosocial behaviour. On the other hand, female peer educators are characterized by a higher level of defending behaviours. These findings may guide further investigation about the role of peer educator in regards to bullying and cyberbullying prevention and intervention programs.